Tinjauan Yuridis Terhadap Pembentukan Peraturan Daerah Kota Tangerang Nomor 7 Tahun 2005, tentang Pelarangan Pengedaran dan Penjualan Minuman Beralkohol - Tedy Subrata (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Formation, Regional Regulation of Tangerang City, Supervision of Cancellation Revocation, Process of Formation of Regional Regulation of Tangerang City Number 7 of 2005, Is it in accordance with Law Number 10 of 2004, concerning Formation of Regulations Per Act and their Implementation, such as Planning, Preparation, Engineering Preparation, Formulation, Discussion, Ratification, Promulgation and Dissemination, but there are Chapters and several Articles, in particular Chapter III concerning Sales and Use Circulation, which are Prohibition or Violation, Article 3 Paragraph (1), Article 4 Letter a, b and c , Article 5 Paragraphs (1) and (2), Article 6 and Article 7 and Chapter VIII, concerning Criminal Provisions, Article 13 Paragraphs (1), (2), (3) and (4) the nature of the sanctions in the form of criminal threats and fines for violators of regional regulations, it turns out to be very contradictory to the Criminal Code Chapter I, concerning Violations of Public Security for People or Goods and Health, Article 492 Paragraphs (1) and (2), in terms of criminal threats and fines for violators of the Criminal Code. in fact it is not as firm as Regional Regulation Number 7 of 2005. What is the Mechanism of Supervision, Revocation and Cancellation, Formation of Regional Regulation Number 7 of 2005, based on Law Number 32 of 2004, concerning Regional Government and Law No. 22 of 2003, concerning the Position Structure MPR, DPR, DPD ·and DPRD Province, Regency and City. This research is a normative legal research which is descriptive and the data is analyzed qualitatively. The result of the research is that the process of formation, supervision, revocation and cancellation is in accordance with Law No. 10 of 2004, Law No. 32 of 2004 and Law No. 22 of 2003.